PENGUATAN KAPASITAS KEBIJAKAN DALAM PENANGGULANGAN BENCANA KEBAKARAN PERMUKIMAN DI KOTA LANGSA - Siti Muthmainnah; M. Akmal; Muhammad Bin Abubakar; Muklir Muklir; Maryam Maryam (FISIP Universitas Malikussaleh, 2026)
This study aims to analyze the policy capacity of local government in addressing residential fire disasters in Langsa City. The research is motivated by the increasing frequency of residential fire incidents in recent years, which have caused significant social and economic losses, yet have not been fully prioritized within regional disaster management policies. Previous studies have largely focused on the technical aspects of fire management, such as risk mapping and physical vulnerability analysis, while limited attention has been given to examining the policy capacity of local governments in managing residential fire risks. This study employs a qualitative approach with a descriptive analytical method. The analytical framework applied is the policy capacity framework developed by Wu, Ramesh, and Howlett, which conceptualizes policy capacity into three main dimensions: analytical capacity, operational capacity, and political capacity operating at the individual, organizational, and system levels. Data were collected through in-depth interviews, document analysis, and literature review of disaster management policy documents in Langsa City. The findings indicate that efforts to strengthen policy capacity have been implemented through the utilization of fire incident data, community-based disaster mitigation programs, and inter-agency coordination in fire response and post-disaster recovery. However, several limitations remain, including insufficient technical training for firefighting personnel, the absence of an independent fire department as firefighting functions remain integrated within the Regional Disaster Management Agency (BPBD), and limited community participation in fire prevention efforts. Therefore, strengthening policy capacity requires improving personnel competencies, reinforcing institutional arrangements for fire services, developing data-driven disaster information systems, and enhancing collaboration among government institutions, communities, and the private sector in mitigating residential fire risks.